PROFIL PENINGKATAN HASIL BELAJAR PRAKTIKUM FISIKA DARING TOPIK HUKUM BOYLE UNTUK MAHASISWA POLITEKNIK NEGERI BANDUNG - I Gede Rasagama (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Physics practicum KBM during the COPID-19 pandemic is unavoidable so that in its implementation certain efforts are needed. Activities carried out for determine the impact of the online Boyle-law practicum that has been designed, about increasing mastery of concepts, increasing ability to work on reports, and perceptions of students' difficulty level with concepts and practical assignments. The research was conducted using a quasi-experimental method and a one group pre-test post-test design. As research subjects were 32 D4 students of POLBAN Energy Conservation Engineering Study Program. The results showed that the online Boyle-law practicum was able to significantly increase the mastery of Boyle-law concepts, from an average score of 33.13 to 46.56 in the low category, and the ability to do reports from an average score of 58.27 to 75.02 in the medium category. The difficulty level of concepts and practical assignments is perceived, each with an average score of 2.68, the category is close to sufficient and the average score is 2.58, the category is close to sufficient.